Thank you for smoking - Buckley, Christopher 1952- (Random House, 1994)
A spoof on the movement to ban smoking. Nick Naylor, a spokesman for the tobacco industry, considers it a privilege to defend the rights of smokers from the neo-puritans, but no one admires him for his idealism. When he is kidnaped by anti-smoking zealots he becomes an instant celebrity and everyone loves him.
Keywords: Smoking -- Fiction; Tobacco industry -- Fiction; Tobacco use -- Fiction; Fiktionale Darstellung; Satire